Sexual Health Decision-Making and Service Utilisation among Kenyan Queer Womxn and Trans Men - Haase, Stephanie (Department of Public Health and Family Medicine, 2023)
Background Queer women and trans men are a neglected populations regarding sexual health status, education, and service provision globally, particularly in low- and middle-income countries. Little is known about their sexual health risk behaviour. In Kenya, the Penal Code criminalises consensual same-sex activity. Public sector health care and information aimed at queer womxn and trans men are lacking, leaving them underserved and at risk of negative sexual health outcomes and other health disparities. Therefore, research is needed to understand the unique sexual health and service needs of Kenyan queer women and trans men and the factors that shape them. Methods Data was collected through a mixed-methods approach in two phases with triangulated quantitative and qualitative elements. A survey based on the literature findings, conceptual models (socioecological model and minority stress model) and previously validated tools was distributed online to a purposive sample of 360 Kenyan queer women and trans men to establish demographics and identify sexual health needs, decision-making, knowledge, behaviour, and barriers to care. Interviews with queer women and trans men were conducted for an in-depth understanding of the factors, experiences, relationships, and health needs that influence decision-making and health-seeking. These were supplemented with interviews with other knowledge-rich stakeholders and expert informants to identify structural barriers as well as feasible solutions to address the gaps. Results The data provided in-depth insight into how Kenyan queer women and trans men's sexual health decision-making and service utilisation are informed. The survey sample represented young, urban, highly-educated queer womxn and trans men. The data identified gaps in all four areas that comprise the socioecological model – societal, community, relationship, personal. Risk behaviours included sexual activities with partners of multiple genders, violence, substance use and low use of barrier methods against pregnancy and sexually transmitted infections. One in three participants had been treated for a sexually transmitted infection in the previous year. Queer womxn and trans men face multiple service-access barriers, many related to stigma and discrimination, as well as fears around provider attitudes. Violations of rights and privacy are a concern. There are insufficient numbers of facilities, programmes, and information to meet the needs of queer womxn and trans men, which results in poor quality of care or patients delaying care. Additional findings suggest that minority stress, including internalised homophobia, external stigma, and concerns around disclosing one's sexual orientation and gender identity, affect the sexual health of Kenyan queer womxn and trans men. Discussion This research found gaps in the sexual health knowledge, the availability of services, and provider attitudes leading to unmet needs around sexual and mental health care. This research demonstrates how restrictive policy and stigmatising environments can contribute to concerns in health and well-being and that the exclusion of queer womxn and trans men's needs is a human rights concern. The findings could be used to inform actions by policy advocates/makers, service providers, educators, and other stakeholders to improve services and tailor information to the needs of queer women and trans men, which could impact their burden of disease and improve quality of life, but also other marginalised populations in low- and middle-income countries.